SAT0591 Consensus Statement for The Evaluation and Management of Patients with Autoimmune and Inflammatory Diseases during Fertility, Pregnancy, Post-Partum and Breastfeeding. (15th July 2016) - Martínez-Lόpez, J.A.; García Vivar, M.L.; Caliz, R.; Loza, E.; Freire, M.; Galindo, M.; Hernández, M.V.; Lόpez Longo, F.J.; Martínez Taboada, V.; Pego Reigosa, J.M.; Rubio, E.; Trujillo, E.; et al.
Abstract : Background: Nowadays there is a great variability in evaluation and management of patients with autoimmune and inflammatory diseases during fertility, pregnancy, post-partum and breastfeeding, in part due to lack of knowledge. Objectives: To develop recommendations on the evaluation and management of patients with autoimmune and inflammatory diseases during fertility, pregnancy, post-partum and breastfeeding based on the best evidence and experience. Methods: Recommendations were generated following nominal group methodology and Delphi technique. A panel of experts was established (12 rheumatologists). A systematic literature review and a narrative review (websites, clinical guidelines and other relevant documentation) were performed and presented to the panel in the 1st panel meeting to be discussed and to help define recommendations. A first draft of recommendations was generated and circulated for comments and wording refinements. A national survey analyzing different aspects of this topic was undertaken separately. Then, a Delphi process (2 rounds) was carried out. Recommendations were voted from 1 (total disagreement) to 10 (total agreement). We defined agreement if at least 70% voted ≥7. The level of evidence and grade or recommendation was assessed using the Oxford Centre for Evidence-based Medicine Levels of Evidence. Results: A total of 14 recommendations (see figure ) were generated on the pre-conception period (oral and hormonal anticonception, reproductive techniques), pregnancy (planning, treatment and follow-up), and breastfeeding (treatment and follow-up). High risk situations were included as lupus or antiphospholipid syndrome. A consensus >90% was reached in all but one recommendation. Conclusions: These recommendations are intended to provide rheumatologists, patients, families and other stakeholders a consensus on the evaluation and management of patients with autoimmune and inflammatory diseases during fertility, pregnancy, post-partum and breastfeeding. Disclosure of Interest: None declared